Transkulturelle Verflechtungen - Mediävistische Perspektiven - Netzwerk Transkulturelle Verflechtungen (Universitätsverlag Göttingen, 2016)
Having elicited much attention in the humanities in recent years, transcultural phenomena will, in all probability, remain a topic of debate in the near future. Being the product of a collaborative act of writing involving nine authors with different specializations, this study is an introduction to the study of phenomena of transcultural entanglement as well as an effort at systematically exploring this field of research from different medievalist perspectives.